Como é que tu diz juron?: Heterodiscurso nas interações entre adultos e crianças ciganas Calon no percurso da aquisição da linguagem - Lima, Marilene Gomes de Sousa (2023)
The main objective of this thesis was to investigate how the heterodiscourse emerges in translanguaging interactions between gypsy adults and children in the process of language acquisition, in order to understand in what ways those children acquire ways of being and acting in a Calon worldview. To this end, I carried out a qualitative field research, through a descriptive-interpretativist basis, in a gypsy community of the Calon trunk, located in Sousa, in the state of Paraíba, Brazil. The fieldwork, which lasted 12 months, allowed my immersion in the context of the daily interactions between adults and two children (a girl – from 20 to 28 months and a boy – from 16 to 29 months) from two families. During that period, which included participant observation, 34 video and audio recordings were made, in addition to field diary entries and interviews. Data were transcribed at ELAN (Eudico Language Annotator) considering vocal production and body movements, and organized into categories based on linguistic-discursive recurrences. The theoretical assumptions that guide the analysis derive from the philosophy of language proposed by Bakhtin's Circle. Based on the understanding of the heterodiscourse as a stratification of language into social-ideological languages, axiological position of the subjects in interaction and the struggle through active social forces, I perform a dialogical exercise of analysis of the interactions between adults and children circumstanced by the presence of a non-gypsy person. The results showed that adults and children in the process of language acquisition mobilize the linguistic repertoire, which, in this community, is composed of Portuguese, Gypsy language, signs, general gestures and gestures specific to those gypsies. Adults, in particular, orchestrate this repertoire to confer Calon alterity in front of their peers and non-gypsy, according to enunciative contexts, that is, in the interested sharing of the other's discourse to the child, which collaborates with the child's insertion in the Calon axiological horizon. Contemplation allowed me to observe the active social forces expressed in the presence of a Juron person in the calon-calon otherness through chibi, a language that is shared only among the Calon. The utterances that presented a repertoire entirely in Portuguese revealed refractions of the signs that indicate the construction of a Portuguese with Calon axiologies. With those reflections, I complete the understanding that the gypsy children of Sousa city enter the discursive stream with their expression in the socio-ideological languages, that is, in the heterodiscourse. This occurs in all cultures, because the living and concrete language is stratified in various combinations. The differences between the groups are the structuring axiological axes and the discursive strategies that each community employs for the heterodiscursive socialization of the children, or rather, in the dynamism of the entire crossing of life. The central axiological axis among the gypsies of Sousa is oriented by the local Calon morality that marks the linguistic materiality of the discursive interaction. About the discursive strategies, I highlight the linguistic games of questions and answers, combined with the use of verbs in the imperative mode triggered by the adults as a resource for interested sharing of the Calon valuative positions in the course of language acquisition. I hope that this thesis will help further studies on language acquisition by looking to Bakhtin's philosophy for elements to guide an understanding of how children and adults position themselves in the world and negotiate meanings in interaction. Finally, the purpose of the results is, besides filling a gap, to raise new questions about language acquisition by gypsy children in Brazil; a subject that is still little addressed by Linguistics, despite the fact that gypsy people have been here since the 16th century.